2021
DOI: 10.1109/tii.2020.2963962
|View full text |Cite
|
Sign up to set email alerts
|

Automated Labeling and Learning for Physical Layer Authentication Against Clone Node and Sybil Attacks in Industrial Wireless Edge Networks

Abstract: In this article, a scheme to detect both clone and Sybil attacks by using channel-based machine learning is proposed. To identify malicious attacks, channel responses between sensor peers have been explored as a form of fingerprints with spatial and temporal uniqueness. Moreover, the machine-learning-based method is applied to provide a more accurate authentication rate. Specifically, by combining with edge devices, we apply a threshold detection method based on channel differences to provide offline training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…is paper is a distributed replica detection program inspired by Ho et al [26]. Related research of clone node detection in MWSN can be found in [45,46].…”
Section: Related Workmentioning
confidence: 99%
“…is paper is a distributed replica detection program inspired by Ho et al [26]. Related research of clone node detection in MWSN can be found in [45,46].…”
Section: Related Workmentioning
confidence: 99%
“…Even though multi-access edge computing is a promising solution for improved services of mobile providers, the security of the data in the edge nodes is a concern [51]. Several applications like connected vehicles, social media apps, healthcare related applications generate the data which is very sensitive [52].…”
Section: Motivations Of the Use Of Blockchain In Eotmentioning
confidence: 99%
“…However, authentication requires high computational resources. A scheme based on channelbased machine learning was proposed in [181] to detect both Clone and Sybil attacks. Simulations and experiments have been carried out in real environments.…”
Section: A Learning-based Countermeasuresmentioning
confidence: 99%